Ethics and management: A controversial issue - Lozano, Josep M. (Journal of business ethics, 1996)
This paper is a part of a broader research project which aims to examine how ethical paradigms are related to theories of organization and management. Using an analysis of various studies on the issue of Business Ethics as its point of departure the paper points out that there are two converging lines of thought. The first emphasizes that management should be reexamined in the light of the cultural changes taking place and maintains that management is a key factor in this change. The second proposes that ethics in general (and Business Ethics in particular) should be understood to mean more than simply “applying certain values” and stresses that this definition of ethics should be rethought in order to foster a closer relationship between ethics and the decision-making processes.